Long-term efficacy of sapropterin in phenylketonuria: a systematic review and meta-analysis of blood phenylalanine reduction, dietary tolerance, and patient-related outcomes - Roberta Leonardi; Manuela Lo Bianco; Annamaria Sapuppo; Concetta Meli; Alessia Migliore; Luisa La Spina; Giuseppina Lanzafame; Maria Grazia Pappalardo; Riccardo Iacobacci; Alessia Arena; Grete Privitera; Martino Ruggieri; et al. (Orphanet Journal of Rare Diseases, 2026)
Abstract Background Phenylketonuria (PKU) is an inherited metabolic disorder caused by mutations in the phenylalanine hydroxylase (PAH) gene, leading to impaired phenylalanine (Phe) metabolism. The mainstay of treatment is a strict low-Phe diet, which can be burdensome. Sapropterin dihydrochloride (Kuvan ® ), a synthetic form of tetrahydrobiopterin (BH4), offers a pharmacological alternative, potentially improving metabolic control and dietary flexibility. However, treatment response varies, and long-term effects remain uncertain. Objective This systematic review and meta-analysis aimed to evaluate the long-term efficacy of Sapropterin in PKU patients, focusing on blood Phe levels, dietary Phe tolerance, and patient-related outcomes such as BMI and IQ. Methods A comprehensive literature search was conducted in PubMed/MEDLINE and Web of Science, following PRISMA guidelines. Studies were included if they reported long-term outcomes of Sapropterin therapy in PKU, assessing Phe levels, dietary tolerance, or patient-related parameters. Meta-analyses were performed using the Wilcoxon rank sum test and forest plots. Results Nineteen studies met the inclusion criteria, with 85 patients providing baseline Phe data and 54 with post-treatment values. Sapropterin significantly reduced blood Phe levels, especially in classic PKU patients with high baseline levels ( p = 0.025). Effects on dietary Phe tolerance were variable, and meta-analysis results were inconsistent. Limited data on BMI and IQ precluded firm conclusions on growth and neurocognition. Genotype analysis ( n = 70) highlighted frequent PAH variants (e.g., p.L48S, p.R261Q), but genotype–response associations remained unclear. Conclusions Sapropterin effectively lowers blood Phe levels in classic PKU, but further studies with standardized measures are needed to clarify its impact on dietary tolerance, growth, cognition, and genotype-based treatment response.